Basic fibroblast growth factor gel preparation induces angiogenesis during wound healing. Issue 3 (March 2023) - Li, Lanfang; Ma, Qiuxiao; Mou, Junyu; Wang, Min; Ye, Jingxue; Sun, Guibo
Purpose: This study aimed to observe the effect of basic fibroblast growth factor (bFGF) gel preparation on wound repair in a full-thickness skin defect rat model and to further explore its mechanism. Methods: The full-thickness skin defect model of Wistar rats was created with circular wounds of 20 mm or 10 mm in diameter on both sides of the spine. The animals were divided into the normal, model, control gel, and bFGF gel groups (300 IU/cm 2 ). The effects of the bFGF gel on wound healing were evaluated and compared. Optical coherence tomography (OCT)-based angiography (OCTA) was used to investigate the effects of bFGF on angiogenesis during wound healing. Western blotting, polymerase chain reaction (PCR), and enzyme-linked immunosorbent assay (ELISA) kits were used to detect the effect of the gel preparation on the levels of vascular endothelial growth factor (VEGF) and matrix metalloproteinases (MMP2 and MMP9) on the wound surface to explore the mechanism. Results: The bFGF gel significantly reduced wound area, promoted the formation of wound granulation tissue, and accelerated wound healing in the bFGF gel group on days 7 and 14, compared with the control gel group. OCTA results showed that bFGF significantly improved wound vascular density, diameter, and circumference. Western blot, PCR, and ELISA results showed that the gel preparation could promote the expression levels of MMP2, MMP9, and VEGF on the wound surface 7 and 14 days after injury. Conclusion: bFGF promotes angiogenesis in wound areas. Topical gel preparations of bFGF can be developed for use in wound repair.